EDIBLE PORTION DAN KANDUNGAN KIMIA IKAN GABUS (Channa Striata) HASIL BUDIDAYA KOLAM DI KABUPATEN KUTAI KARTANEGARA, KALIMANTAN TIMUR - Andi Noor Asikin; Indrati Kusumaningrum (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
Snakehead fish is one kind of fresh water fish which found in swamp, rivers and lakes. Snakehead fish obtained from fishing and cultivation. Snakehead fish contains high protein especially as albumin source for beneficial healthy. This study was aimed to determine edible portion and chemical composition of snakehead fish on three groups size (weight) of snakehead fish from pond cultivation. Snakehead fish were divided in to three groups by weight size : B group (801-1100 gr), S group (501-800 gr), K group (200-500 gr). Procedure was carried out by measurement of fish body and proximate analysis. The result showed the highest edible portion was found on B group and lowest edible portion in K group. The highest water content found on K group were 78.63% and the lowest on S group were 77.17%.The highest protein content found on B group were 18.12% and the lowest on S group were 17.14%. The highest fat content found on S group were 2.43% and the lowest on K group were 2.05%. The highest carbohydrate found on B group were 0.91% and the lowest on K group were 0.72%. The highest ash content found on S group were 1.79% and the lowest ash content on K group were 1.36%.